Thematic Physical Education Games Model for Grade 1 Elementary School Student - Satyawan, I Made; Dartini, Ni Putu Dwi Sucita (Prodi PGSD Penjas FPOK UPI, 2021)
The application of thematic learning in Physical Education, Sports, and Health subject in Grade 1 Elementary School often faces difficulties due to the lack of physical activity reading sources and literatures that can be used as examples of activities. The purpose of this study was to develop an integrated thematic-based Physical Education game model for Grade 1 Elementary School on My Favorite theme. The research method used was the RD method developed by Borg and Gall. In the research stage, the initial developed product had been validated by 3 validators, consisting of design experts, content/material experts, and field practitioners. The product of this research was a thematic Physical Education games for Class 1 on My Favorite theme module consisting of 8 types of games adjusted to the theme and sub-theme. The results of the expert validation test obtained 93% (a very good category) for the design, 93% (a very good category) for the content/materials, and 88.75% (a good category) for the practitioner perception. It concludes that the thematic-based Physical Education game model is feasible and can be used in Physical Education learning. Teachers can use this thematic Physical Education game module as a reading source and examples of Physical Education learning activities.